INVESTIGATION OF THE INFLUENCE OF PARTICLE SIZE DISTRIBUTION OF SAND ON THE EFFECTIVENESS OF SAND PROVIDING SYSTEM LOCOMOTIVE - Buhaienko, V. V.; Osenin, Yu. I. (Science and Transport Progress, 2009)
A process of interaction of the running-on air stream and the particle of an abrasive material on a way section from an exhaust outlet of sanding plant to a place of locomotive wheel/rail contact is considered. The mathematical model of movement of a particle is built. The trajectories of movement of particles of different sizes are calculated at various values of initial velocity and speed of a running-on air stream. Recommendations for choice of granulometric composition of the used abrasive material are given.